Suppression of Obsessive-Compulsive Symptoms after Head Trauma - Seyed Hamzeh Hosseini; Paria Azari; Roohollah Abdi; Reza Alizadeh-Navaei (Case Reports in Medicine)
Obsessive-Compulsive Disorder (OCD) encompasses a spectrum of clinical symptoms characterized by unwanted thoughts coupled with an intense compulsion to act and to repeat behavior fragments in a ritualistic and stereotyped sequence. Obsessive-compulsive symptom due to brain lesions is not rare, but suppression of these symptoms after head trauma is very rare and we found only 3 cases in review of literatures from 1966 to 2001. The case of a patient suffering with severe OCD is described of note; her symptoms disappeared following right temporo-parietofrontal lesion.